2014
DOI: 10.3233/aic-130586
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid automatic scoring system for Arabic essays

Abstract: Essay writing is widely used for student performance assessment. This paper presents a hybrid automatic essay scoring system (AES) for Arabic essays. The system attempts at saving the time teachers spend on reading and scoring Arabic essays. It utilizes latent semantic analysis (LSA) and three linguistic features (i.e., word stemming, number of words and number of spelling mistakes). This paper also describes an algorithm to determine the optimal reduced dimensionality used in LSA. To evaluate the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Experiment results showed that the addition of LSA over syntactic features improves the scoring performance of AES (Omar & Mezher, 2016). Many contents similarity-based AES used LSA or any of its variations in deriving grades or scores (Awaida et al, 2019;Amalia et al, 2019;Alghamdi, et al, 2014;Contreras et al, 2018;Ong et al, 2011;Shehab et al, 2018).…”
Section: Content Similarity Frameworkmentioning
confidence: 99%
“…Experiment results showed that the addition of LSA over syntactic features improves the scoring performance of AES (Omar & Mezher, 2016). Many contents similarity-based AES used LSA or any of its variations in deriving grades or scores (Awaida et al, 2019;Amalia et al, 2019;Alghamdi, et al, 2014;Contreras et al, 2018;Ong et al, 2011;Shehab et al, 2018).…”
Section: Content Similarity Frameworkmentioning
confidence: 99%
“…This method relies on generating vectors-presentation for semantic terms, words, or even the concepts [19]. Research in [20] presented a system for scoring Arabic short answers by embedding LSA with the main three important syntactic features: lemmatization, the mistake of words, and the number of common words. They employed bag-of-words (BOW) to present feature vectors that mapped into the Cosine algorithms to measure the similarity between student answers (SAs) and model answers (MAs).…”
Section: Related Workmentioning
confidence: 99%
“…Corpus-based [17], [20], [21], [23] Arabic automated short answer scoring Hybrid approaches (String-based, Corpus based) [8], [24].…”
Section: Arabic Automated Online Exam Scoringmentioning
confidence: 99%
“…A system based on the basis of stemming methods and processes editing Levenshtein to evaluate the students' exams online was provided [27]. Therefore, a hybrid method for an automatic essay scoring system (AES) for Arabic articles was suggested [28]. The system relies mainly on light and heavy stemming of words, whereby it relies only on a string-based algorithm (Levenshtein).…”
Section:  Levenshtein Distance Similaritymentioning
confidence: 99%